A Fully Solution‐Printed Photosynaptic Transistor Array with Ultralow Energy Consumption for Artificial‐Vision Neural Networks. Issue 18 (28th March 2022) - Shi, Jialin; Jie, Jiansheng; Deng, Wei; Luo, Gan; Fang, Xiaochen; Xiao, Yanling; Zhang, Yujian; Zhang, Xiujuan; Zhang, Xiaohong
Abstract: Photosynaptic organic field‐effect transistors (OFETs) represent a viable pathway to develop bionic optoelectronics. However, the high operating voltage and current of traditional photosynaptic OFETs lead to huge energy consumption greater than that of the real biological synapses, hindering their further development in new‐generation visual prosthetics and artificial perception systems. Here, a fully solution‐printed photosynaptic OFET (FSP‐OFET) with substantial energy consumption reduction is reported, where a source Schottky barrier is introduced to regulate charge‐carrier injection, and which operates with a fundamentally different mechanism from traditional devices. The FSP‐OFET not only significantly lowers the working voltage and current but also provides extraordinary neuromorphic light‐perception capabilities. Consequently, the FSP‐OFET successfully emulates visual nervous responses to external light stimuli with ultralow energy consumption of 0.07–34 fJ per spike in short‐term plasticity and 0.41–19.87 fJ per spike in long‐term plasticity, both approaching the energy efficiency of biological synapses (1–100 fJ). Moreover, an artificial optic‐neural network made from an 8 × 8 FSP‐OFET array on a flexible substrate shows excellent image recognition and reinforcement abilities at a low energy cost. The designed FSP‐OFET offers an opportunity to realize photonic neuromorphic functionality with extremely low energy consumption dissipation. Abstract : A fully solution‐printed photosynaptic organic field‐effect transistor is developed by introducing a source Schottky barrier. Both working voltage and current are substantially lowered, giving rise to an ultralow energy consumptions of 0.07–34 fJ per spike in short‐term plasticity and 0.41–19.87 fJ per spike in long‐term plasticity, which are comparable with biological synapses.